Strategy design for New Public Governance and horizontal initiatives. (25th November 2021) - Taylor, Emily; Schwartz, Robert; Trowbridge, Joslyn; Di Ruggiero, Erica; Sullivan, Terry; Marchildon, Gregory; Dobrow, Mark; Finegood, Diane; Price, Alex
Abstract: Governments deploy comprehensive strategies to address complex social problems with various New Public Governance and horizontal initiatives. Minimal attention, however,  has focused on developing evidence‐informed strategy design for such initiatives. Using a systematic literature review, five strategy design principles were identified: 1) proper selection of interventions; 2) system enablers; 3) a guiding purpose; 4) substantive political commitment; and 5) joined‐up governance. Three case studies including document review and interviews tested strategy design principles. Empirical work supported, expanded, and further refined these principles. Application of these principles would likely contribute to improving the success of horizontal strategy initiatives. Real‐world political pressures and public administration constraints can be somewhat alleviated through learnings from well‐designed strategies and experiences. Sommaire: Les gouvernements utilisent des stratégies globales pour répondre à des problèmes sociaux complexes avec diverses initiatives horizontales et de la Nouvelles gouvernance publique. Néanmoins, ces initiatives n'ont recu que peu d'attention en ce qui concerne l'élaboration d'une conception stratégique fondée sur des données probantes. À l'aide d'un examen systématique de la littérature, nous avons identifié cinq principes de conception stratégique : 1) une sélection appropriée des interventions; 2) des facilitateurs du système; 3) un objectif directeur; 4) un engagement politique réel; et 5) une gouvernance conjointe. Trois études de cas comprenant un examen de documents et des entretiens ont testé les principes de conception stratégique. Ces principes ont été soutenus, élargis et affinés par des travaux empiriques. L'application de ces principes contribuerait probablement à améliorer le succès des initiatives stratégiques horizontales. Les enseignements tirés de stratégies et d'expériences bien conçues peuvent pallier les pressions politiques du monde réel et les contraintes de l'administration publique.